Strategi Coping Petani Dalam Mencari Tambahan Pupuk (Studi pada Masyarakat Desa Ngampel Kecamatan Ngusikan Kabupaten Jombang) - Pratama, Dimas Tirta (Paradigma, 2023)
Abstract The policy on the management of subsidized fertilizer recommendations is a policy change in the world of agriculture. The aim of this policy is for sustainable agriculture with attention to environmental balance. However, this policy actually caused problems for the farmers in Ngampel Village. The problems felt after the implementation of the subsidized fertilizer recommendation management policy resulted in a small amount of subsidized fertilizer received by farmers. Obtaining subsidized fertilizer obtained is very less than the need for fertilizer that farmers need for each season.The purpose of this research is to find out the coping strategies used by farmers in looking for additional fertilizer. This study uses qualitative research methods which originate from primary data collection, namely observation, interviews and documentation. Secondary data from searching journals, articles, and books with related themes is accompanied by a coping theory perspective from Lazarus & Folkman to analyze the data.The results of the study show that the impact of the subsidized fertilizer recommendation governance policy that is felt by farmers includes 3 aspects, namely: social aspects, economic aspects, and cultural aspects. The coping strategies used by farmers to solve this problem are divided into two types, namely: coping strategies that focus on problems and coping strategies that focus on emotions.As for small, medium, and large land farmers, each has a coping strategy to solve the problem of restrictions related to subsidized fertilizers.Coping strategies that focus on problems are carried out by adding relationships,owe, seling part of the crop, modifying production methods, affiliating with fellow farmers, seeking alternative solutions to agricultural extension workers, and affiliating with fertilizer shops/agents. Meanwhile, coping strategies that focus on emotions are carried out in a resigned manner because the farmer’s resources cannot change the policy. The findings of this study indicate that the problem solving actions taken by farmers tend to be problem-focused coping strategies rather than emotion-focused coping strategies. Kebijakan tata kelola rekomendasi pupuk subsidi adalah sebuah kebijakan perubahan di dunia pertanian. Tujuan dari kebijakan ini adalah untuk pertanian berkelanjutan dengan memperhatikan keseimbangan lingkungan. Kebijakan ini menyebabkan permasalahan tersendiri bagi petani di Desa Ngampel. Permasalahan yang dirasakan pasca adanya kebijakan tata kelola rekomendasi pupuk subsidi menyebabkan perolehan pupuk subsidi yang diterima petani menjadi sedikit. Perolehan pupuk subsidi yang diperoleh sangat kurang dari kebutuhan pupuk yang petani butuhkan untuk setiap musimnya. Tujuan dari penelitian ini adalah untuk mengetahui strategi coping yang dilakukan petani dalam mencari tambahan pupuk. Penelitian ini menggunakan metode penelitian kualitatif yang bersumber pada pengumpulan data primer yaitu observasi, wawancara dan dokumentasi. Data sekunder dari penelusuran jurnal, artikel, dan buku dengan tema terkaitdisertai dengan perspektif teori coping dari Lazarus & Folkman untuk menganalisis data. Hasil penelitian menunjukkan bahwa dampak kebijakan tata kelola rekomendasi pupuk subsidi yang dirasakan oleh petani meliputi 3 aspek, yaitu: aspek sosial, aspek ekonomi, dan aspek budaya. Strategi coping yang digunakan petani untuk menyelesaikan masalah ini terbagi menjadi dua jenis, yaitu: strategi coping yang berfokus pada masalah dan strategi coping yang berfokus pada emosi. Adapun petani lahan sempit, sedang, sampai luas masing-masing memiliki strategi coping untuk menyelesaikan masalah pembatasan terkait pupuk subsidi. Strategi coping yang berfokus pada masalah dilakukan dengan cara menambah relasi, berhutang, menjual sebagian hasil panen, memodivikasi cara produksi, berafiliasi dengan sesama petani, mencari alternatif solusi ke penyuluh pertanian, serta berafiliasi dengan toko/agen penjual pupuk. Sedangkan strategi coping yang berfokus pada emosi dilakukan dengan cara pasrah sebab sumberdaya petani tidak bisa mengubah kebijakan tersebut. Temuan penelitian ini menunjukkan bahwa tindakan penyelesaian masalah yang diambil petani lebih cenderung kepada strategi coping yang berfokus pada masalah ketimbang strategi coping yang berfokus pada emosi. Keywords: Farmers; Coping Strategie; Governance; fertilizer; Agriculture